Turats and the Reconstruction of Scientific Civilization in Progressive Muslim Perspective - Yusdani, Yusdani; Abdi, Supriyanto (RSF Conference Series: Business, Management and Social Sciences, 2023)
This paper examines the intellectual responses of the progressive variant of Muslim thought to various contemporary humanity’s challenges based on its distinctive epistemological and interpretive approach, namely progressive ijtihad. This is library research based on analyzing the works of leading proponents of this progressive Muslim thought. It argues that progressive Muslim thought offers and develops a critical and progressive interpretation of Islam that respects and glorifies human values. With this epistemological and interpretive framework, progressive Muslim thought contributes significantly to the development and reconstruction of scientific civilization, which is transdisciplinary and capable of tackling various humanity’s problems at both global and local levels.